(3TQM GdhGajIs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CfYeG HLhOg haVdg hcQeG abhdg daX JTed GdcdeI hZjQgG dCfg de jJdaX Hg s
(3BNQgG (B:s
(3hde jMQchgG aQbkG HjfgG hHjf GdJfhjf LYdhG deG jONd GdCSeGA Ydi eG jONd GdCaYGd eRjI gPG BNQ TQM GdhGajI s
(3HChdgG agQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs